Título Padrão - Bezerra Vettorazzi, Mayra; Vieira Faria, Vicente (Arquivos de Ciências do Mar, 2020)
Manuel Antonio de Andrade Furtado Neto was a pioneer researcher in the field of population, conservation, and evolutionary genetics of marine vertebrates in Brazil. He was one of the first scientists in the country to apply the now-famous polymerase chain reaction (PCR) technique to aquatic organisms. He provided, in the 1990s, the first genetic evidence to suggest that the Guiana Dolphin (South American Atlantic Coast) and the Tucuxi (Amazon Basin) were distinct species. At that time, Guiana and Tucuxi dolphins were still considered a single species, Sotalia fluviatilis – the species level divergence between them was only confirmed by other colleagues in the following decade. He was also at the forefront of applying techniques of molecular markers to other marine organisms in the country, including snappers, tuna, lobsters and sharks. Among these, the study of the molecular phylogeny of angelsharks stands out, having been, until now, the only study to generate and make publicly available a DNA sequence of the Critically Endangered Argentine Angelshark, Squatina argentina.